ANALYSIS OF THE EFFICIENCY OF BUDGET EXECUTION OF TERRITORIAL COMMUNITIES UNDER THE CONDITIONS OF MARITAL STATE - Ірина Фаринович; Орися Волошин (Економіка та суспільство)
The article examines the effectiveness of the implementation of the local budget during the period of martial law. The dynamics of the formation of budget revenues analyzed. The results of the analysis of the implementation of the budget of the territorial community showed that the main source of filling the revenue part of the budget is tax revenue, in particular the tax on the income of individuals. The dynamics and structure of budget expenditures of the Truskavet territorial community studied. Revealed that budget expenditures are growing significantly, especially expenditures on financing education, statewide functions, and housing and communal services. Found that the effective formation and implementation of local budgets depends on the state of hostilities in one or another region. Established that despite the growing need for spending, the budget of the Truskavet Territorial Community is being implemented with a surplus. Despite the problems caused by the martial law, the territorial community is able to effectively form and use budget funds. Proven that the sustainable socio-economic development of the community depends on the balance of the budget, i.e. the effectiveness of its implementation. The effectiveness of local budget execution can be assessed by various indicators, such as the coefficient of stability and independence of the budget, the coefficient of budget effectiveness, budget deficit/surplus. These indicators help to assess how effectively local authorities manage budget funds and fulfill their responsibilities to the community. It was found out that the coefficients of budget efficiency in terms of general budget revenues and tax revenues increased during the studied period. It is substantiated that the Truskavets territorial community is dependent on transfers. This is confirmed by the decrease in the indicator of budget performance based on income without transfers. In today's difficult conditions, the local government should use all opportunities for financial support of the community through interaction with business, enterprises, and organizations. We suggest to the Truskavets territorial community to focus on the development of tourism and a sanatorium-hotel resort.